Review of Energy Consumption by the Fish Farming and Processing Industry in Croatia and the Potential for Zero-Emissions Aquaculture - Tena Bujas; Marija Koričan; Manuela Vukić; Vladimir Soldo; Nikola Vladimir; Ailong Fan (Energies, 2022)
Higher energy efficiency and lower environmental impact have become very important aspects in the evaluation of the design and operation of technical systems. The same goes for the fish farming sector, which continuously aims to reduce its environmental footprint as well as its operating costs. This paper reviews the energy needs of the fish farming sector and their impact on the environment, and discusses the possibilities of improving the environmental friendliness of this sector by employing a higher share of renewable energy sources. The fish farming process is divided into its constitutive phases: fish breeding with associated activities, transportation, and handling of grown fish, together with relevant processes; and final processing and distribution to the customers. For these phases, the energy consumption and associated emissions, depending on the energy source, have been assessed. The parts of the process with the highest potential for the integration of alternative powering options and consequent environmental improvements are identified. The case study deals with the fish farming process in Croatia, for which a set of alternative powering options has been proposed, considering the existing energy supply, i.e., import of fossil fuels and current Croatian electricity mix, as well as renewable energy potential, which is reviewed in the paper.